Patient Safety Incident Differences Between Accredited and not Accredited Primary Health Center - Arlina Dewi; Nevi Seftaviani; Erna Rochmawati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The study aims to identify the differences of patient safety incident (PSI) by health workers in accredited and non-accredited Primary health care (PHC) by its frequency and severity of harm. This research used analytic crossectional method. A well-structured questionairre of 15 patients’ safety indicators was administered to collect response of Nurse and midwife in 3 accredited PHC and 3 non-accredited PHC about patients’ safety incident in last month. In the result, overall the incident happened more frequent in non-accredited PHC than in acrredited PHC which is statistically significant (CI 95%, p=0.002). Specifically, what the nurses handle is about medication (CI 95% p=0.018) and therapeutic treatment (CI 95% p=0.036). Also, it is about the education (CI 95% p=0.025) and documentation (CI 95% p=0.013). Still, two indicators of midwife’s treatment while transferring and about the education involved minor harm.